Crime and gender: a study on how men and women are represented in international crime statistics - Heiskanen, Markku (Publication series, 2016)
The task is to find out how men and women are represented in the criminal justice process, ranging from the suspects as recorded by the police, to the enforcement of sentences. The aim is to show the level of differences in offender rates by gender, to study changes in offender rates by gender, and to present indicators of attrition by gender. The crime categories explored are total crime, homicide, rape, assault, theft and fraud. The study is based on crime statistics from two sources, the Crime Trends Survey coordinated by the United Nations Office on Drugs and Crime, and the European Sourcebook of Crime and Criminal Justice Statistics.